Optimalisasi Analisis Optimalisasi Baznas Kota Bandar Lampung dalam Meningkatkan Kesadaran Muzakki Membayar Zakat - Mahdoli Mahdoli; Diah Mukminatul Hasyim (Journal of Creative Student Research, 2024)
A person's desire to pay zakat is influenced by personal interests driven by various factors such as feelings, hopes, and tendencies. Zakat is not only considered a religious obligation for Muslims, but also as a wealth distribution system that can reduce socio-economic disparities. This study aims to assess the effectiveness and efficiency of BAZNAS Bandar Lampung City in increasing the awareness of muzakki to pay zakat. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research findings show that BAZNAS Bandar Lampung City is effective in increasing the awareness of muzakki through socialization, understanding, openness, and cooperation with other institutions. The efficiency of BAZNAS is reflected in the increase in zakat funds collected from 2018 to 2022, although there was a decrease in 2022 due to the management of zakat carried out independently by mosques in Bandar Lampung.